A novel fatigue cohesive model for interface between ballastless track slab and self-compacting concrete. (9th May 2023) - He, Lan; Wang, Jinfeng; Wu, Xi; Wang, Guannan; Wang, Yutong; Chu, Haowei
Highlights: F-CZM is proposed for describing fatigue bond performance of interface in a ballastless track. Fatigue degradation laws of the interface in a ballastless track are established. Interface fatigue life curves and interfacial separating displacement curves are acquired. DIC is used to monitor the evolution of full-field strain distribution of specimens. Abstract: The interface between track slab and concrete is the weakest zone in a ballastless track. Under the long-term and repeated coupling effect of the environment and train loads, a large area of damage can occur at this interface, leading to the initiation and propagation of interlaminar crack, and the failure of the interlayer bonding area. To reveal the fatigue behaviors and degradation laws of the interface between the prefabricated track plate (C60) and self-compacting concrete (SCC) in China Railway Track System (CRTS) III slab track, a fatigue cohesive zone model is proposed for the analysis of the fatigue bonding performances of the interface C60-SCC, and the fatigue damage degradation criterion is established. Next, static and fatigue tests for C60-SCC composite specimens are conducted, and full-field strain distribution images of these specimens are obtained by the digital image correlation technique. The results show that: (1) the evolution of interfacial crack of C60-SCC specimens under monotonic loading was captured and static cohesive parameters were obtained; (2) the fatigue life curve and interfacial separating displacement curves were acquired, for predicting the interface fatigue life and calculating the degree of interface damage and residual fatigue life of CRTS III slab track in service; (3) the fatigue cohesive response of the interface C60-SCC under cyclic loading were determined for describing the fatigue behaviors of the interface in CRTS III slab track.